Effect of fish, starch and salt contents on the microstructure and expansion of fish crackers ('keropok') - Cheow, C.S.; Yu, S.Y.; Howell, N.K.; Che Man, Y.; Muhammad, Karidah (Wiley, 1999)
Light microscopy studies on the fish cracker gel and expanded product ('keropok') emphasised the role of fish proteins in the starch expansion process. The addition of salt (20 g kg-1) in the 'keropok' helped to distribute evenly the starch in the fish protein. Formation of thin fish muscle bundles assisted the expansion of 'keropok'. At 700-900 g kg-1 fish content, the fish muscle bundles formed a continuous network that caused a drop in the 'keropok' expansion. From the scanning electron microscopy study, ridges were found in samples (containing 600-900 g kg-1 fish content) with 20 g kg-1 salt at high magnification.